Company Profile Gerakan Pemuda Ansor Kecamatan Kartasura Berbasis Website - Muhammad Khasan Sandi Khasan; Diyah Ruswanti (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2024)
ABSTRACT The development of information and communication technology has a significant impact on various sectors, including youth organizations. GP Ansor Kartasura District faces challenges in managing information and member interactions with conventional methods, such as direct meetings and WhatsApp messages. This study aims to develop a web-based information system to improve communication efficiency, member data management, and publication of organizational activities. Research methods include literature studies, observations, and interviews. System development used the waterfall model with needs analysis, system design, implementation, integration, and maintenance. The results indicate that this web-based information system can overcome information delays, improve interaction between members, and facilitate data management. The implementation of this system is expected to support organizational management and increase member participation in GP Ansor Kartasura District activities.